El deporte como herramienta para la estimulación de las capacidades biopsicosociales con la población de CEPAS de la Universidad del Quindío. (2019)
The development of this study was of great importance because in this population do not develop in-depth sports projects due to lack of commitment to the student community for the development of proposals involving vulnerable populations by providing an alternative to the stimulation of their capacities biologías and psychosocial. This project helped to teach these communities of vulnerable children through the sport may also occupy his free time, so that you can achieve a better communication, relationship and integration with the society. The project allowed to give the importance of physical activity, the benefits it brings to the practice, as this will inculcara a lifestyle a little more healthy, awakening the interest for the sport in this population. Were 72 kinds of sport in which they demonstrated the importance of conducting this type of projects that involved the participation of the most vulnerable communities where activities were held recreational sports, thus favouring a good stimulation of their capabilities, biopsychosocial, and also to a better use of your free time and make them understand the importance of physical activity.